Work stress (Work Stress Network, 2017)
"This handbook has been produced by the WorkStress Network (UK National Work Stress Network). Consists of unpaid volunteers bringing together workplace trade union and health and safety representatives, academics, safety professionals and others to campaign for the better protection of workers against stress-related mental and physical illnesses caused by poorly controlled workplace psycho-social hazards. The handbook examines: The problem - The extent of work-related stress illness - The cost of work-related stress illnesses to the individual, society and the economy - The causes of work-related stress - The effects of stress on the mental and physical health of workers - Obstacles to progress - The law The solution - Preventing work stress (the role of government, employers, trade unions and individuals) - Conducting a risk assessment - Dealing with individual stress"